Beginning Google Blogger - Wright-Porto, Heather (Apress, 2012)
Beginning Google Blogger is an easy-to-read, how-to book about Blogger, loaded with step-by-step instruction and visual aids detailing many aspects of creating and managing a Blogger blog. You will learn basic concepts and advanced techniques, from creating a new blog and selecting fonts and colors to converting the blog to a three-column layout and installing custom blog graphics. You will also learn how to set up a domain name and create a navigational bar.